2014
DOI: 10.1371/journal.pone.0102760
|View full text |Cite
|
Sign up to set email alerts
|

Lavage with Allicin in Combination with Vancomycin Inhibits Biofilm Formation by Staphylococcus epidermidis in a Rabbit Model of Prosthetic Joint Infection

Abstract: Background and AimThe present anti-infection strategy for prosthetic joint infections (PJI) includes the use of antibiotics and surgical treatments, but the bacterial eradication rates are still low. One of the major challenges is the formation of biofilm causing poor bacterial eradication. Recently it has been reported that allicin (diallyl thiosulphinate), an antibacterial principle of garlic, can inhibit bacteria adherence and prevent biofilm formation in vitro. However, whether allicin could inhibit biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…Lavage with lipophilic allicin combined with vancomycin inhibited biofilm formation by S. epidermidis in a rabbit model of prosthetic joint infection (Zhai, Pan, Pang, & Bai, ). In a pilot study of patients with denture stomatitis, a mouthwash with garlic aqueous extract was superior to nystatin primarily due to less adverse effects (Bakhshi, Taheri, Shabestari, Tanik, & Pahlevan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lavage with lipophilic allicin combined with vancomycin inhibited biofilm formation by S. epidermidis in a rabbit model of prosthetic joint infection (Zhai, Pan, Pang, & Bai, ). In a pilot study of patients with denture stomatitis, a mouthwash with garlic aqueous extract was superior to nystatin primarily due to less adverse effects (Bakhshi, Taheri, Shabestari, Tanik, & Pahlevan, ).…”
Section: Discussionmentioning
confidence: 99%
“…The time-kill assay revealed that aqueous garlic extract showed better antiproteolytic effects on total Porphyromonas gingivalis protease activity compared with ethanolic garlic extract (Shetty, Thomas, Shetty, Bhandary, & Shetty, 2013 Lavage with lipophilic allicin combined with vancomycin inhibited biofilm formation by S. epidermidis in a rabbit model of prosthetic joint infection (Zhai, Pan, Pang, & Bai, 2014). In a pilot study of patients with denture stomatitis, a mouthwash with garlic aqueous extract was superior to nystatin primarily due to less adverse effects (Bakhshi, Taheri, Shabestari, Tanik, & Pahlevan, 2012).…”
Section: Fermented Black Garlicmentioning
confidence: 99%
“…Many studies have shown that GE, as a naturally occurring antibacterial substance, has a good antibiofilm effect. 11,17,41,42 A previous study reported the eradication of biofilms of MDR bacteria. 36 Garlic ointment prevented biofilm formation of S. aureus, S. epidermidis, P. aeruginosa, Acinetobacter baumannii and K. pneumoniae.…”
Section: Characteristics Of Prosthesis-related Infectionsmentioning
confidence: 99%
“…12 There are many reports about allicin inhibiting bacterial adherence and preventing biofilm formation in vitro. 11,41,42 However, whether this property still works in vivo remains unknown. A previous study established an artificial knee joint infection model in rabbits and divided the rabbits into four groups, which were lavaged with normal saline, allicin, vancomycin or allicin plus vancomycin for 14 days.…”
Section: Characteristics Of Prosthesis-related Infectionsmentioning
confidence: 99%
See 1 more Smart Citation